Green supply chain management – experience from some enterprises in the world and lessons for Vietnamese enterprises - Lê Thị Thu Trang; Nguyễn An Giang (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Green supply chain  and green supply chain management are two strong development trends recently in the world, including Vietnam. The problems of global warming, greenhouse, effects, natural disasters, air and water pollution, epidemics, etc. are of interest not only for States and global organizations but also for enterprise and every citizen. The article focuses on "green" business, solve the problem of how to reorganize enterpries’s supply chain, to make it more cost effective and energy efficient, focus on customers more, waste less, produce more, grow more sustainably and be environmentally friendly. The article is researched from an enterprise perspective, learn about green supply chain management in general, and experience from some world enterprises such as IBM, Wal-Mart and SC Johnson & Son are well known in green supply chain management. The data of the article is aggregated from information in the press releases, websites of research enterprises, and from the research results of famous scientists in supply chain management such as David Blanchard, Michael H. Hugos.